Tissue-Specific Oxidative Stress Modulation by Exercise: A Comparison between MICT and HIIT in an Obese Rat Model. (14th July 2019) - Groussard, Carole; Maillard, Florie; Vazeille, Emilie; Barnich, Nicolas; Sirvent, Pascal; Otero, Yolanda F.; Combaret, Lydie; Madeuf, Elise; Sourdrille, Antoine; Delcros, Geoffroy; Etienne, Monique; Teixeira, Allison; et al.
Abstract : Background and Aim . Exercise is an effective strategy to reduce obesity-induced oxidative stress. The purpose of this study was to compare the effects of two training modalities (moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT)) on the pro/antioxidant status of different tissues in obese Zucker rats. Methods . Eight-week-old male Zucker rats ( fa / fa, n = 36 ) were subdivided in three groups: MICT, HIIT, and control (no exercise) groups. Trained animals ran on a treadmill (0° slope), 5 days/week for 10 weeks (MICT: 51 min at 12 m·min -1 ; HIIT: 6 sets of 3 min at 10 m·min -1 followed by 4 min at 18 m·min -1 ). Epididymal (visceral) and subcutaneous adipose tissue, gastrocnemius muscle, and plasma samples were collected to measure oxidative stress markers (advanced oxidation protein products (AOPP), oxidized low-density lipoprotein (oxLDL)), antioxidant system markers (ferric-reducing ability of plasma (FRAP), superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPx) activities), and prooxidant enzymes (NADPH oxidase and xanthine oxidase (XO) activities, myeloperoxidase content). Results . Compared with the control, MICT increased GPx and catalase activities and the FRAP level in epididymal adipose tissue. HIIT increased the AOPP level in subcutaneous adipose tissue. In the muscle, HIIT increased both SOD and GPx activities and reduced the AOPP level, whereas MICT increased only SOD activity. Finally, plasma myeloperoxidase content was similarly decreased by both training modalities, whereas oxLDL was reduced only in the MICT group. Conclusion . Both HIIT and MICT improved the pro/antioxidant status. However, HIIT was more efficient than MICT in the skeletal muscle, whereas MICT was more efficient in epididymal adipose tissue. This suggests that oxidative stress responses to HIIT and MICT are tissue-specific. This could result in ROS generation via different pathways in these tissues. From a practical point of view, the two training modalities should be combined to obtain a global response in people with obesity.